Chemical Quality Of Milk From Ettawa-Crossed Goats During Various Lactation Periods In Tunggulo Village, Limboto District, Gorontalo Regency - Rokhayati, Umbang Arif; Nugroho, Tri Ananda Erwin (International journal of technology and education research, 2026)
PE goats are a dual-purpose goat breed, used for both milk and meat production. Goat milk is a source of animal protein that is increasingly in demand by the public. The chemical quality of goat milk is thought to vary from farm to farm. This study aims to determine the quality of Ettawa crossbred goat milk during various lactation periods in Tunggulo Village, Limboto District, Gorontalo Regency. This research was conducted from January to March 2026 at the Animal Husbandry Laboratory, Faculty of Agriculture, Gorontalo State University. The method used was a case study. The data used consisted of primary and secondary data. The parameters tested were fat and protein content. The average protein content between the 1st, 2nd, 3rd, and 4th lactations was 5.38%; 5.15%; 5.03%; and 4.83%, respectively. The average fat content between the 1st, 2nd, 3rd, and 4th lactations was 5.11%; 4.16%; 4.44%; and 6.31%, respectively. It was concluded that the highest protein content was found in P1 (Lactation 1) at 5.38%, while the highest fat content was found in P4 (Lactation 4) at 6.31%.